Frequency of Hypertension and Diabetes Millitus in Patients Presenting With Acute Ischemic Stroke (Medical Forum Monthly, 2024)
Objective: To find the frequency of hypertension and diabetes mellitus in patients with acute ischemic stroke.Study Design: Descriptive / cross sectional study.Place and Duration of Study: This study was conducted at the Medicine, Qazi Hussain Ahmad Medical Complex, Nowshera Medical College, and Nowshera. One year from July 2018 to June 2019.Materials and Methods: 100 patients of acute ischemic stroke were collected by convenient (non-probability) sampling technique. Patients fulfilling the inclusion criteria were further assessed through a detailed history from patients or from relatives, CT scan brain, random and fasting blood sugar, lipid profile, chest x-ray and ECG was done in all patients.Results: Hypertension was present in 45% patients. Hypertension and diabetes mellitus was present in 24% cases, 23% patients were not having any of these diseases. Diabetes mellitus was present in only 8% cases.Conclusion: Hypertension and diabetes collectively are the two main risk factors for ischemic stroke. The frequency of diabetes mellitus alone was very low in this study.